Passages from India: Indian anti‐colonial activism in exile, 1905–20. Issue 248 (29th May 2014) - Aziz, Zaib un Nisa
Abstract: As one of the first anti‐colonial movements of the twentieth century, the Indian struggle for independence has attracted a vast and rich historiography. Much of this has been focused within the boundaries of India. This article adds a transnational dimension by examining Indian anti‐colonial activism in exile. The experience of political exile, both voluntary and involuntary, provides insight into the international dimensions of radical politics. This article tells the story of some of these exiled revolutionaries, looking at radical Indian nationalists in London (1905–10); the emergence of the Ghadar movement in the United States (from 1914); and the early career of anti‐colonial revolutionary M. N. Roy (1917–19). It gauges the impact of global events including the First World War and the Bolshevik revolution on the thoughts, ideas, movements, collaborations and confrontations of these actors.